Metals Accumulation in Muscle Tissues and Digestive Contents of Periglypta reticulata (Kerang Geton) from Lancang Island, Jakarta - Suratno Suratno; Rachma Puspitasari; Zahriza Purnadayanti; Novita Sandra (Indonesian Journal of Chemistry, 2020)
The concentration of nineteen metals (Hg, As, Cd, Co, Cr, Cu, Fe, Li, Mg, Mn, Mo, Ni, Pb, Se, Sr, Ti, Tl, V, and Zn) were determined in muscle tissues and digestive contents of Periglypta reticulata (Kerang Geton), collected from Lancang Island part of Seribu Islands, Jakarta. An interaction between toxic and essential metal in a clam is also studied. The results showed high concentrations of As (4.56), V (1.20), and Zn (4.91) mg/kg wet weight in muscle tissues and As (7.16), Ti (2.53), and Zn (8.68) mg/kg wet weight in digestive contents. Average concentrations of metals in muscle tissues and digestive contents were below regulation limit from permissible standard National Agency of Drug and Food Control except for Arsenic (As). The average concentration of metals in muscle tissues was significantly (P < 0.05) lower than in digestive contents except As, Co, Cr, Mg, and Tl, respectively. Toxic metals (Pb, Hg, Cd, and As) showed a strong correlation with several essential metals so that these metals can be a threat to the main function of a particular metal. The present study showed digestive contents could accumulate in higher metals; therefore, we suggested removing it before consuming this clam.